Experimental Study of Oil Displacement and Gas Channeling during CO2 Flooding in Ultra—Low Permeability Oil Reservoir - Feng Liu; Ping Yue; Qingli Wang; Gaoming Yu; Jiangtang Zhou; Xiukun Wang; Quantang Fang; Xinxin Li (Energies, 2022)
Aiming to solve the problems of poor CO2 displacement efficiency and serious gas-channeling and low well-opening rates in ultra-low permeability reservoirs, we carry out CO2 displacement experiments under different permeability reservoirs by using different development methods, water drive to gas drive procedures, and different fracture positions to clarify the effects of physical formation properties, injection methods, and fracture parameters on CO2 displacement efficiency in C8 ultra-low permeability reservoirs. The experimental results show that the recovery degree of CO2 miscible drive increases with an increase in permeability. When the gas–oil ratio is greater than 2000 m3/m3, serious gas channeling can be observed in both the miscible drive and immiscible drive. In addition, when the water drive is altered to be a gas drive, the water cut of 0.45 mD and 0.98 mD cores decreased, and the recovery degree increased by 13.4% and 16.57%, respectively. A long fracture length will deteriorate gas channeling and lower the CO2 oil-displacement efficiency. However, the fracture location is found to have little impact on the recovery of CO2 displacement.